USING GROUNDWATER LEVELS TO ESTIMATE RECHARGE - Healy R.W.; Cook P.G. (My University, 2002)
Accurate estimation of groundwater recharge is extremely important for proper management of groundwater systems. Many different approaches exist for estimating recharge. This paper presents a review of methods that are based on groundwater-level data. The water-table fluctuation method may be the most widely used technique for estimating recharge; it requires knowledge of specific yield and changes in water levels over time. Advantages of this approach include its simplicity and an insensitivity to the mechanism by which water moves through the unsaturated zone. Uncertainty in estimates generated by this method relate to the limited accuracy with which specific yield can be determined and to the extent to which assumptions inherent in the method are valid. Other methods that use water levels (mostly based on the Darcy equation) are also described. The theory underlying the methods is explained. Examples from the literature are used to illustrate applications of the different methods.
Keywords: GROUNDWATER RECHARGE; GROUNDWATER HYDRAULICS; GROUNDWATER FLOW; GENERAL HYDROGEOLOGY